Raw Data from Network analysis reveals underlying syntactic features in a vocally learnt mammalian display, humpback whale song - Jenny A. Allen; Ellen C. Garland; Rebecca A. Dunlop; Michael J. Noad (2019)
This file contains the data used in this study